Short-term Safety of a Silicone Gel–filled Breast Implant: A Manufacturer-sponsored, Retrospective Study. Issue 5 (May 2020) - Yoon, Seanhyuck; Chang, Jae-Hoon
Abstract : Background: Currently, 8 different brands of a silicone gel–filled breast implant are commercially available in Korea. But the superiority of short-term safety has not been established. Methods: A total of 709 patients (1, 418 breasts) received an implant-based augmentation mammaplasty. We compared a 1-year incidence of complications and complication-free survival among the breast implants. Moreover, we performed a subgroup analysis of the patient cohorts by excluding cases associated with a periareolar incision, revision or reoperation, and anatomic implants. Results: In our series, 1-year incidences of complications were 0.55% (1/182), 3.14% (5/159), 5.19% (7/135), and 6.58% (10/152) in patients receiving the BellaGel/BellaGel SmoothFine, the Mentor CPG, the Matrix, and the Motiva Ergonomix, respectively. Moreover, the incidence of capsular contracture was 0.55%, 0.63%, 1.32%, and 3.70% in patients receiving the BellaGel/BellaGel SmoothFine, the Mentor CPG, the Motiva Ergonomix, and the Matrix, respectively. Furthermore, a complication-free survival was 24.82 ± 0.18, 22.23 ± 1.09, 22.15 ± 0.77, and 22.12 ± 1.07 months in patients receiving the BellaGel/BellaGel SmoothFine, the Motiva Ergonomix, the Mentor CPG, and the Matrix, respectively, except for the 2 other remaining products used for a smaller number of patients. However, a subgroup analysis showed no significant differences in a 1-year incidence of complication and complication-free survival among the BellaGel SmoothFine, the Motiva Ergonomix, and the Naturgel. Conclusion: It is impossible to draw a definite conclusion about the superiority of the short-term safety among the silicone gel–filled breast implants that are commercially available in Korea.